Increase in heterotrophic soil respiration by temperature drives decline in soil organic carbon stocks after forest windthrow in a mountainous ecosystem. (19th December 2016) - Mayer, Mathias; Sandén, Hans; Rewald, Boris; Godbold, Douglas L.; Katzensteiner, Klaus
Summary: Intensifying forest disturbance regimes are likely to impact heavily on future carbon (C) budgets of forest ecosystems. Our understanding of how forest disturbance affects the sources of soil CO2 efflux ( F s ) is, however, poor. This may lead to uncertainties over future C sink estimates of forest ecosystems and associated feedbacks to the atmosphere. We investigated the impact of forest windthrow on the heterotrophic and autotrophic sources of F s, underlying biotic and abiotic drivers (i.e. plant community composition, soil organic matter (SOM) properties and soil microclimate), and consequences for soil organic carbon (SOC) stocks in situ along a disturbance chronosequence in the European Alps. This chronosequence facilitated the study of temporal changes in the above parameters between the third and sixth years after windthrow. Along the chronosequence, structural equation modelling revealed that soil temperature, soil moisture, SOM properties and plant community composition explained 90% of the variation in F s . While no direct interactions among plants and SOM properties could be determined, plants significantly affected soil microclimate. Windthrow had no obvious effect on F s because reduced autotrophic soil respiration ( R a ) was offset by a ∼60% increase in heterotrophic soil respiration ( R h ), principally due to increased soil temperatures. R a after wind‐throw was dominated by grasses and herbs rather than trees; however, a high abundance of ectomycorrhizal fungi suggests an important indirect tree contribution to post‐windthrow R a . SOC stocks significantly declined over the post‐windthrow period. Our results show that R h was by far the dominant source of F s after forest windthrow. As C losses from R h and SOC stocks were in the same order of magnitude, this study demonstrates that post‐windthrow declines in SOC stocks were mainly driven by a temperature‐related increase in R h . A lay summary is available for this article. Abstract : Lay Summary